An intra‐cultural investigation in Brazil using Coalho cheese and preferred attribute elicitation. Issue 1 (30th October 2019) - Soares, Eveline K. B.; Silva, Ramon; da Silva, Wanessa P.; Kuriya, Shigeno P.; Maçaira, Paula M.; Cyrino Oliveira, Fernando L.; da Silva, Maria A. A. P.; Pimentel, Tatiana C.; Freitas, Mônica Q.; Cruz, Adriano G.; Esmerino, Erick A.
Abstract: This study aimed to evaluate the application of preferred attribute elicitation (PAE) methodology for assessing the perceptions of consumers from different regions of Brazil (Northeast, Southeast or South, n = 20) about Coalho cheese samples. Northeast Brazilian consumers elicited a higher number of attributes (22 vs. 13–15) and had a higher frequency of consumption (3 vs. 1.3–1.6 times a week), while those from South region had higher reliability ( RV = 0.95) with a low number of consumers ( n = 16). Consumers from different Brazilian regions elicited common sensory descriptors considered important for Coalho cheese characterization, such as yellow color, presence of eyes, brightness, Coalho cheese aroma, salty taste, bitter taste, acid taste, and rubbery texture. Furthermore, there was no impact of the region on the acceptance of the products. In conclusion, Brazilian consumers from different regions characterized the Coalho cheeses in a similar manner, and PAE methodology could be used in intra‐cultural investigations, being recommended a minimum of 19 consumers. Practical Applications: Consumer based methodologies are gaining popularity in the sensory and consumer science. This is the first study that evaluated the application of PAE methodology regards an intra‐cultural consumer perception using as stimulus Coalho cheese, a typical Brazilian cheese. The findings are relevant to improve the processing of the Coalho cheese taking in account the consumer perception as well as to develop efficient marketing strategies of commercialization of this product.